PENGARUH MODEL PEMBELAJARAN MATEMATIKA KNISLEY (MPMK) TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MIPA SMAN NEGERI 1 SOLOK - Jamaluddin Ashari (Departemen Matematika, 2022)
Mathematics Learning result can be an indicator of the success of a learning process. However, the result of mathematics learning in second grade of science major at SMA Negeri 1 Solok is still low. At least, the main reason is that the learning model used in class does not make student active in learning process. Therefore, we need a learning model that can make learning outcomes better than before. In this research the researcher use a model called Knisley Learning Model. Knisley has four stages in its implementation, where there is a different division of roles between teacher and student in each step of learning. The purpose of this research is to describe and find out whether the learning outcomes of students who use Knisley Learning Model are better than students who learn with direct learning in XI classes at SMAN 1 Solok. This research use Quasi-experimental method with Non-equivalent control where only group design as reseacrh design. Based on related data analysis, the reaseracher found that there is an effect where mathematics learning outcomes learned by applying Knisley learning model are better than mathematics learning outcomes learned with direct learning models in XI MIPA classes at SMAN 1 Solok. Keywords– Knisley, Mathematics learning, Mathematical result, learning outcomes